The constitutional structure of proportionality - Klatt, Matthias; Meister, Moritz (Oxford : Oxford University Press, 2012)
Proportionality is one of the most important principles in constitutional law, relevant throughout jurisdictions worldwide. Setting out the state of the art proportionality doctrine, this book combines theoretical reconstruction with case-law examples defending and developing the dominant model.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Proportionality in law; Constitutional law